2005
DOI: 10.1021/jo0521044
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced 1,4-Additions of Indoles to Enones

Abstract: [reaction: see text] A photoinduced procedure for the 1,4-addition of indoles to enones is described. This reaction occurs with modest to excellent yield for cyclic and some acyclic enones. This reaction is experimentally simple, requiring only irradiation (UVA lamps, ca. 350 nm) of the reagents in a CH2Cl2 solution at room temperature, and avoids the necessity to use a Lewis acid. An important solvent effect was noticed, with CH2Cl2 and CHCl3 being the optimal solvents. Various substituents are tolerated on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The clay promoted FriedelCraft alkylation of indole to enone and amido sulfones were also investigated [43,44]. Michael addition of indoles to enones was also investigated over photoinduced 1,4-additions [45]. Reddy et al reported the Michael addition of indoles onto en-1,4-dione for synthesis of 3-(1-(1H-indol-3-yl)-2-oxo-2-phenylethyl)indolin-2-one as antibacterial and antifungal agent using iodine as a catalyst [46].…”
Section: Introductionmentioning
confidence: 99%
“…The clay promoted FriedelCraft alkylation of indole to enone and amido sulfones were also investigated [43,44]. Michael addition of indoles to enones was also investigated over photoinduced 1,4-additions [45]. Reddy et al reported the Michael addition of indoles onto en-1,4-dione for synthesis of 3-(1-(1H-indol-3-yl)-2-oxo-2-phenylethyl)indolin-2-one as antibacterial and antifungal agent using iodine as a catalyst [46].…”
Section: Introductionmentioning
confidence: 99%
“…A photoinduced procedure for the 1,4-addition of indoles to enones was described by Moran et al 3 The procedure is simple to carry out requiring only irradiation in CH 2 Cl 2 solution at room temperature and it has the added advantage of avoiding the need for a Lewis acid. The indole unit can be variously substituted, although an electronic trend was reported, with electron-withdrawing groups suppressing the reaction.…”
Section: Organic Synthesismentioning
confidence: 99%
“…Hopf et al described a new method for the preparation of [n]ladderanes in moderate yields, based on a one-pot [2 + 2] photocycloaddition of [2.2]paracyclophane pseudo-gem bis(polyene) precursors. The [3]-and [5]ladderanes were isolated and fully characterized, including by X-ray structure analysis. 14 In addition the compounds showed some photochromic properties such as reversible change from yellow or red to colourless forms.…”
Section: Organic Synthesismentioning
confidence: 99%
“…Indole can be functionalized at each position around its aromatic structure through various transformations. Traditionally, the C3-positions of indole molecules have been widely used as nucleophiles to react with a variety of electrophiles in both enantioselective ( Austin and MacMillan et al, 2002 ; Zhou and Tang et al, 2002 ; Evans et al, 2005 ; Wang et al, 2006 ; Terada et al, 2007 ; Bandini et al, 2009 ; Joucla and Djakovitch et al, 2009 ; Bartoli et al, 2010 ) and non-chiral fashion ( Bartoli et al, 2005 ; Kimura et al, 2005 ; Moran et al, 2006 ; Kusurkar et al, 2008 ; Lerch et al, 2014 ). Transition metals, amines and Lewis acids are frequently used as effective catalysts for these reactions.…”
Section: Introductionmentioning
confidence: 99%